Differences in Virulence Between Legionella pneumophila Isolates From Human and Non-human Sources Determined in Galleria mellonella Infection Model - Sousa, Patrícia S.; Silva, Inês N.; Moreira, Leonilde M.; Veríssimo, António; Costa, Joana (Frontiers in Cellular and Infection Microbiology, 2018)
Legionella pneumophila is a ubiquitous bacterium in freshwater environments and in many man-made water systems capable of inducing pneumonia in humans. Despite its ubiquitous character most studies on L. pneumophila virulence focused on clinical strains and isolates from man-made environments, so little is known about the nature and extent of virulence variation in strains isolated from natural environments. It has been established that clinical isolates are less diverse than man-made and natural environmental strains, suggesting that only a subset of environmental isolates is specially adapted to infect humans. In this work we intended to determine if unrelated L. pneumophila strains, isolated from different environments and with distinct virulence-related genetic backgrounds, displayed differences in virulence, using the Wax Moth Galleria mellonella infection model. We found that all tested strains were pathogenic in G. mellonella, regardless of their origin. Indeed, a panoply of virulence-related phenotypes was observed sustaining the existence of significant differences on the ability of L. pneumophila strains to induce disease. Taken together our results suggest that the occurrence of human infection is not related with the increased capability of some strains to induce disease since we also found a concentration threshold above which L. pneumophila strains are equally able to cause disease. In addition, no link could be established between the sequence-type (ST) and L. pneumophila pathogenicity. We envision that in man-made water distribution systems environmental filtering selection and biotic competition acts structuring L. pneumophila populations by selecting more resilient and adapted strains that can rise to high concentration if no control measures are implemented. Therefore, public health strategies based on the sequence based typing (STB) scheme analysis should take into account that the major disease-associated clones of L. pneumophila were not related with higher virulence in G. mellonella infection model, and that potential variability of virulence-related phenotypes was found within the same ST.